SIGNIFICANCE OF SINGLE-NUCLEOTIDE POLYMORPHISMS 2578C>A AND +936C>T IN THE VEGF GENE FOR EFFICIENCY EVALUAT ION OF ANTICANCER IMMUNOTHERAPY IN PAT IENTS WITH METASTAT IC SKIN MELANOMA - Yu. A. Khochenkova; G. Z. Chkadua; I. V. Samoylenko; T. F. Malivanova; I. N. Mikhailova; L. V. Demidov; E. V. Stepanova (Медицинская иммунология)
Abstract. Increased VEGF levels in cancer patients may be associated with decreased number of dendritic cells (DCs) and lower DC function. We investigated whether VEGF gene polymorphisms -2578C>A (rs699947) and +936C>T (rs3025039) are associated with efficacy of autologous DC-based immunotherapy in patients with malignant melanoma. Evaluation of VEGFR-1 and VEGFR-2 expression on mature monocyte-derived DC revealed a decreased VEGFR-1 level (18.9±0.7% on peripheral blood monocytes, as compared to 6.3±0.6% on mature DCs) and non-changed VEGFR-2 expression (13.1±0.4% and 15.9±0.4%, respectively). The АА genotype frequency of -2578C>A (rs699947) polymorphism of VEGF gene was 46.1%. АС heterozygous state was found in 38.5%, and СС, in 15.4% of cases. The VEGF -2578 AC and AA genotypes were directly associated with progression-free survival and efficacy of treatment. The median progression-free survival of patients with -2578 AA and AC genotypes was a significantly longer (8.4 months), as compared with that of patients with CC genotypes (2.7 months), p = 0.002. The established relationship between genotype and efficacy of immunotherapy can be used to develop modern methods for predicting melanoma progression and to personalize immunotherapy including a combination with antiangiogenic therapy.